2015
DOI: 10.4238/2015.december.29.23
|View full text |Cite
|
Sign up to set email alerts
|

Combination of edaravone and neural stem cell transplantation repairs injured spinal cord in rats

Abstract: ABSTRACT. This study sought to observe the effect of the combination of edaravone and neural stem cell (NSC) transplantation on the repair of complete spinal cord transection in rats. Eighty adult female SpragueDawley (SD) rats were used to establish the injury model of complete spinal cord transection at T9. Animals were divided randomly into four groups (N = 20 each): control, edaravone, transplantation, and edaravone + transplantation. The recovery of spinal function was evaluated with the Basso, Beattie, B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…The second evaluation was the MRI, which showed in the EB-treated group, a diffuse hyperintense sclerotic plaque in the T2-weighted and axial scan and hypointense sclerotic plaque in the T1-weighted scan. The SVF co-treated group had a decrease in lesion intensity on the T1-weighted, T2-weighted, and axial scans as mentioned by [ 66 ] in the dog with spinal cord injury and [ 67 ]. This is unlike the study mentioned by [ 62 ], which found no improvement in MRI lesions after stem cell injection.…”
Section: Discussionmentioning
confidence: 78%
“…The second evaluation was the MRI, which showed in the EB-treated group, a diffuse hyperintense sclerotic plaque in the T2-weighted and axial scan and hypointense sclerotic plaque in the T1-weighted scan. The SVF co-treated group had a decrease in lesion intensity on the T1-weighted, T2-weighted, and axial scans as mentioned by [ 66 ] in the dog with spinal cord injury and [ 67 ]. This is unlike the study mentioned by [ 62 ], which found no improvement in MRI lesions after stem cell injection.…”
Section: Discussionmentioning
confidence: 78%
“…For instance, NSC transplantation together with erythropoietin injection has been reported to positively affect axon regeneration in adult rats having suffered transected spinal cord injuries (Zhao et al, 2015). In addition, a combination of edaravone and NSC transplantation has been shown to repair injured spinal cords in a rat model (Song et al, 2015). Moreover, GM1 and NGF synergistically effect neurite regeneration, neurofilament protein upregulation, and stimulation of neuritogenesis (Bolsover, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Transplanting neural stem cells construct significant improvement in spinal cord-injured animal models, especially, at the acute phase of injury by means of axonal growth promotion as well as lost cell replacement (Cheng et al, 2017;Iwanami et al, 2005;Lu, Jones, Snyder, & Tuszynski, 2003). Thus, the low efficiency of NSCs transplantation is a challenging problem (Lin et al, 2016), whereas, combinational therapy, the chemical application along with NSCs, may provide a protective circumstance for transplanted NSCs survival and operation (Hosseini et al, 2018;Lane, Lepore, & Fischer, 2017;Song, Peng, & Ye, 2015;Zhang & Shen, 2015).…”
Section: Introductionmentioning
confidence: 99%